A Model of Balanced Living in Disruptive Age According to Anupubbikathā - Uppapakdee, Tunsamorn; Ruksat, Suvin; Ploychum, Suchao (Journal of Dhamma for Life, 2025)
This dissertation article is the qualitative research with in-dept interview and has 5 objectives listed as followings: 1) to study the living in disruptive age 2) to study the living according to Anupubbikathã 3) to present the model that can reinforce the balance-living in disruptive age according to Anupubbikathã 4) to present the way and the body of knowledge of Balanced Living in Disruptive Age According to Anupubbikathã. The research results are as followings: 1) The ways of living in disruptive age are being pushed into an unbalance-states in 3 aspects: society, economics and environment. These characteristics in disruptive age could be described as BANI which is stand for Brittle; Anxious; Nonlinear and Incomprehensible respectively. 2) Living according to Anupubbikathã which is composed of 5 guidelines. The first one is the way of sharing. The second one is to act harmony with the rules and precept. The third one is the way to achieve the happiness of common people. The fourth one is being in awareness the insights of five sensual pleasure. The last one is the way to live sufficiently with every day dhamma practice. 3) A model of the Living according to Anupubbikathã can reinforce the balance-living in disruptive age These 5 guidelines can reinforce into the motivation of the basic needs of all human being.4) The way and the body of knowledge of Balanced Living in Disruptive Age According to Anupubbikathã was presented as the Model called “SHE IS E Model”.